The Relationship Between Art and Politics in the 19th Century Ottoman Empire: Institutionalization, Change and Continuity - Komsuoglu, Aysegul; Toker, Hikmet; Nardella, Federica (Istanbul University Press, 2021)
In the 19th century, the Ottoman Empire's social, economic, military, and political structures changed. Military officers began to study the Western nations' technical and institutional structures to understand and resolve the causes of recent defeats and subsequent loss of land. Modernization efforts that began in the military field evolved into a movement to modernize all institutional structures. The Empire's intention to adapt to a rapidly changing world was evident in the widespread modernization of all fields, from art and agriculture to education and transportation. The reforms had some peculiar features. One such feature is continuity between old and new structures. During this time, modernization caused an abrupt change in art. The most significant change was the institutionalization of plastic, visual, and performing arts. Many art institutions were founded between the second half of the 19th century and the first half of the 20th century. New regulations were drafted to modernize art foundations. Musical ensembles were converted into formal establishments. However, these new establishments did not replace either old structures and educational systems or their traditional elements. This coexistence of old and new allowed for continuity between the two, enabling different "worlds" to exist simultaneously. It also allowed different forms and mentalities across the Ottoman world to merge. Artists and administrators familiar with old and new systems played an important role in the construction of continuity in the Empire. Another change was the politicization of art; for example, music was used to construct power symbols. Given its political use in the process of modernization of the Ottoman Empire, art can be seen as a significant component of the new Ottoman identity. "The Relationship between Art and Politics in the 19th Century Ottoman Empire: institutionalization, Change and Continuity" is an interdisciplinary reading of change and continuity in the Empire's period of modernization within the context of art and politics. We discuss how changes in the political, economic, and social spheres and the intervention of important figures and events affected various forms of art through different dynamics of change and continuity. The authors of this book are scholars working in different fields of the social sciences, bringing an interdisciplinary approach to the subject matter.